Direct Determination of a Bare Neutron Counter Yield Function. Issue 4 (27th March 2020) - Nuntiyakul, W.; Mangeard, P.‐S.; Ruffolo, D.; Evenson, P.; Bieber, J. W.; Clem, J.; Hallgren, A.; Madsen, J.; Pyle, R.; Sáiz, A.; Tilav, S.
Abstract: Ground‐based neutron counters are a standard tool for detecting atmospheric showers from GeV range primary cosmic rays of either solar or galactic origin. Bare neutron counters, a type of lead‐free neutron monitor, function much like standard neutron monitors but have different yield functions primarily because they are more sensitive to neutrons of lower energy. When operated together with standard monitors, the different yield functions allow estimates to be made of the energy spectrum of galactic or solar particles. In 2010 a new array of 12 bare neutron detectors was installed at the South Pole to operate together with the neutron monitor there. Prior to installation, two of the detectors were operated on a ship that traveled from Sweden to Antarctica and back from November 2009 to April 2010. The purpose of this latitude survey was to use Earth's magnetic field as a spectrometer, blocking cosmic rays below the local cutoff rigidity (momentum per unit charge), from which we determined the response function versus rigidity of these bare counters. By comparing that measured response function to direct measurements of the cosmic ray spectrum taken by the PAMELA spacecraft, we were able to make a direct determination of the yield function for these detectors. Key Points: Bare neutron counters characterize the energy spectrum of high‐energy solar particles when used together with a neutron monitor Bare neutron counters aboard a ship measured secondary cosmic rays over a wide range of magnetic latitudes Simultaneous measurements of the primary cosmic ray spectrum by spacecraft allow a direct determination of the bare neutron counter yield function